2020
DOI: 10.1186/s40478-020-01025-1
|View full text |Cite
|
Sign up to set email alerts
|

Unclassified four-repeat tauopathy associated with familial parkinsonism and progressive respiratory failure

Abstract: We describe an autopsied patient with familial parkinsonism and unclassified four repeat-tau (4R-tau) aggregation. She presented with bradykinesia, truncal dystonia, and mild amnesia at the age of 61 and then exhibited body weight loss (15 kg over 8 months), sleep disturbances, and progressive respiratory failure with CO 2 narcosis. She died of respiratory failure at the age of 62, 14 months after disease onset. Her brother also showed parkinsonism at the age of 58 and suddenly died 6 mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…As noted in the introduction, deposition of 4R tau aggregates is associated with a range of neurodegenerative disorders, such as progressive supranuclear palsy, corticobasal degeneration, FTDP-17, argyrophilic grain dementia, globular glial tauopathy, ageingrelated tau astrogliopathy, others [33][34][35][36]. Post-mortem studies have revealed tau aggregations throughout brain regions in a form of dense and prominent plagues, either neuronal or glial, distributed in equal measure in astrocytic processes and oligodendroglia [37][38][39]. After years of studying clinical cases and designing experimental models of tau pathology, more than 25 tau mutations have been identified to date [40], although the vast majority of the mutations remains unattributed to the known tau-related neurodegeneration causing dementia.…”
Section: Discussionmentioning
confidence: 98%
“…As noted in the introduction, deposition of 4R tau aggregates is associated with a range of neurodegenerative disorders, such as progressive supranuclear palsy, corticobasal degeneration, FTDP-17, argyrophilic grain dementia, globular glial tauopathy, ageingrelated tau astrogliopathy, others [33][34][35][36]. Post-mortem studies have revealed tau aggregations throughout brain regions in a form of dense and prominent plagues, either neuronal or glial, distributed in equal measure in astrocytic processes and oligodendroglia [37][38][39]. After years of studying clinical cases and designing experimental models of tau pathology, more than 25 tau mutations have been identified to date [40], although the vast majority of the mutations remains unattributed to the known tau-related neurodegeneration causing dementia.…”
Section: Discussionmentioning
confidence: 98%
“…However, in tauopathy it oligomerises and then forms aggregates with a range of conformations [ 38 ], resulting in distinct neuropathological lesions in each tauopathy [ 26 ]. Many tauopathies have a bias towards one tau isoform over the others [ 21 , 38 , 87 , 103 ] and the isoform of tau appears to influence the rate of aggregation with 4R isoforms aggregating the most rapidly [ 121 ]. It is not yet understood why this is the case.…”
Section: Tau Isoforms Are Dysregulated In Tauopathiesmentioning
confidence: 99%
“…In AD, ex vivo tau fibrils appear to be predominantly twisted, while nontwisting fibrils have not been documented. However, ribbon-like tau fibrils with no twist or only occasional twists have been reported in multiple system tauopathy with presenile dementia ( 40 ), in an unclassified 4R tauopathy associated with familial parkinsonism and progressive respiratory failure ( 41 ), and in an AD mouse model ( 42 ). Although the modern cryoEM technique is highly efficient for determining amyloid fibril structures, the technique requires fibril twists, thus nontwisting fibrils have largely escaped attention.…”
Section: Discussionmentioning
confidence: 99%